Automatic offloading method of loop statements of software to FPGA. Issue 5 (3rd September 2021) - Yamato, Yoji
Abstract : With Moore's law coming to an end, using hardware other than central processing units (CPUs), such as more energy efficient field-programmable gate arrays (FPGAs), has recently been increasing. However, when using heterogeneous hardware other than CPUs, barriers of technical skills, such as in using Open Computing Language (OpenCL), are high. Therefore, I previously proposed environment-adaptive software that enables automatic conversion, configuration, and high-performance operation of once-written code according to the hardware to be placed. Offloading of some applications to graphics processing units (GPUs) was automated previously. In this paper, I proposed an automatic offloading method of appropriate target loop statements of applications as the first step in offloading to FPGAs. I evaluated the effectiveness of the proposed method by applied it to multiple applications.